Diagnosis and management of acute enteropathogens in returning travelers. (October 2022) - Ross, Allen G.; Khanam, Farhana; Islam, Md. Taufiqul; Chowdhury, Fahima; Sleigh, Adrian C.
Highlights: Acute enteropathogens are a common cause of gastrointestinal illness in travelers Initial clinical assessment is critical in determining the severity of disease Diagnosis typically comprises culture, enzyme-linked immunosorbent assay, or polymerase chain reaction Management depends on the severity of dehydration and the infectious organism Vaccines are available for only some of the acute enteropathogens